Obesity in Rural Indonesia: Examining the Effects of BTS Towers, Age and Gender - Zahrani, Ayu; Davina, Aifa Putri; Arrantissi, Syauqi Hanif; Sulastijah, Siti; Farida, Dany; Candrasari, Anika; Firda, Fathiyyatu Assadiy; Romadhon, Yusuf Alam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Obesity is a significant global health issue, including in Indonesia, where its prevalence continues to rise. This study investigates the influence of Base Transceiver Station (BTS) towers, age, and gender on obesity in rural Indonesian communities. A cross-sectional study analyzed secondary data from 9,639 patient visits to the Gatak Subdistrict Health Center between May and July 2024. Body Mass Index (BMI) was categorized into normo/underweight and overweight/obese groups, while BTS tower data were obtained from regional statistics. Statistical analyses were conducted using bivariate (Pearson's Chi-square) and multivariate (binary logistic regression) methods. Results showed that the presence of BTS towers and age did not significantly influence obesity. However, gender was a significant factor, with women exhibiting a higher prevalence of overweight/obesity compared to men (aOR = 0.796, p = 0.000). Most patients lived in areas with fewer than three BTS towers, and the majority were classified as normo/underweight. In conclusion, gender significantly influences obesity prevalence, with women being more affected than men, while the presence of BTS towers and age showed no significant relationship with obesity. These findings underscore the need for further research to explore additional factors contributing to obesity in rural Indonesian populations.